2020
DOI: 10.1088/1361-6501/aba37d
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic probe calibration using Gaussian process regression

Abstract: During the calibration of an aerodynamic probe, the correlation between the present representative flow quantities of the fluid and the measurand is determined. Thus, a large number, sometimes several thousands, of different calibration points are set and measured, making this a very time-consuming process. The differences in the calibration data of similar constructed probes are very small. With the help of statistical methods, more precisely Gaussian process regressions, this similarity is exploited in order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Sensor calibration and cross-sensitivity compensation are receiving growing attention in the wider field of ML [33]- [35], [38], [39], [42]- [45]. In this section, we position our work based on Bayesian learning, regression, and design of experiment within the context of these studies, which have relied on support vector machines (SVMs) [34], random forests (RFs) [34], [38], [39], Gaussian process regression (GPR) [39], [42], [43], and artificial neural networks (ANNs) taking most often the form of multilayered perceptrons (MLP) [33], [34], [44], [45] and fuzzy neural networks (FNNs) [35], among other methodologies [34].…”
Section: B Comparison With Other ML Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sensor calibration and cross-sensitivity compensation are receiving growing attention in the wider field of ML [33]- [35], [38], [39], [42]- [45]. In this section, we position our work based on Bayesian learning, regression, and design of experiment within the context of these studies, which have relied on support vector machines (SVMs) [34], random forests (RFs) [34], [38], [39], Gaussian process regression (GPR) [39], [42], [43], and artificial neural networks (ANNs) taking most often the form of multilayered perceptrons (MLP) [33], [34], [44], [45] and fuzzy neural networks (FNNs) [35], among other methodologies [34].…”
Section: B Comparison With Other ML Methodsmentioning
confidence: 99%
“…As an alternative, random forests have successfully been applied to the calibration of multi-pollutant sensors [38] and of NO 2 and particulate matter (PM 10 ) sensors [39]. Thirdly, GPR has been applied to the calibration of thermal and differential-pressure anemometers [42], NO 2 and particulate matter (PM 10 ) sensors [39], and capacitive artificial skin sensors [43].…”
Section: B Comparison With Other ML Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the reconstruction of the flow-field properties, the measured pressures are post-processed taking the calibration data of both, temporal and spatial, calibrations into account. A high reconstruction accuracy below 0.2 • in both flow angles and 0.1 m/s in the reconstructed velocity can be achieved, as shown in Heckmeier and Breitsamter (2020). Pretests have shown that the temporal characteristics of the probe are limited due to bandwidth restrictions of the transfer function in the temporal calibration.…”
Section: Methodsmentioning
confidence: 88%
“…Given that pressure varies with altitude, probes used in aircraft applications are equipped with an additional series of reading ports, called the static ring, where static pressure is measured. The probes are calibrated before their usage in flight conditions and can resolve flow angles up to with high precision [ 6 ].…”
Section: Introductionmentioning
confidence: 99%